2022
DOI: 10.1002/ange.202112063
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Catalytic Mechanism of the Endoperoxide Synthase FtmOx1

Abstract: The 2‐oxoglutarate (2OG)‐dependent non‐heme enzyme FtmOx1 catalyzes the endoperoxide biosynthesis of verruculogen. Although several mechanistic studies have been carried out, the catalytic mechanism of FtmOx1 is not well determined owing to the lack of a reliable complex structure of FtmOx1 with fumitremorgin B. Herein we provide the X‐ray crystal structure of the ternary complex FtmOx1⋅2OG⋅fumitremorgin B at a resolution of 1.22 Å. Our structures show that the binding of fumitremorgin B induces significant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“… Accordingly, NvfI introduces three oxygen atoms in one catalytic cycle of the nonheme iron enzyme. This feature of the NvfI reaction is different from the reaction of the previously characterized Fe­(II)/αKG-dependent fumitremorgin B endoperoxidase FtmOx1, which only installs the endoperoxide group without forming an additional hydroxyl group. Furthermore, assays using 18 O 2 and H 2 18 O suggested that the two oxygen atoms in the endoperoxide are derived from molecular oxygen while the oxygen atom in the hydroxyl group is derived from water, indicating that solvent exchange processes occur during the NvfI reaction.…”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 63%
“… Accordingly, NvfI introduces three oxygen atoms in one catalytic cycle of the nonheme iron enzyme. This feature of the NvfI reaction is different from the reaction of the previously characterized Fe­(II)/αKG-dependent fumitremorgin B endoperoxidase FtmOx1, which only installs the endoperoxide group without forming an additional hydroxyl group. Furthermore, assays using 18 O 2 and H 2 18 O suggested that the two oxygen atoms in the endoperoxide are derived from molecular oxygen while the oxygen atom in the hydroxyl group is derived from water, indicating that solvent exchange processes occur during the NvfI reaction.…”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 63%
“…(1) Does the proximal Tyr residue (Y94 in CthEgtB or Y377 in MthEgtB) function as a redox-active residue by donating an H atom (Scheme 1a), or as a general acid-base catalyst in assisting proton transfer (route I in Scheme 1b)? Even though redoxactive Tyr residues are found to be involved in the catalysis of many other non-heme enzymes, [34][35][36][37][38][39][40][41][42][43][44] kinetic experiments tend to support the general acid-base role of this proximal Tyr residue in EgtB.…”
Section: Introductionmentioning
confidence: 99%